Principles and Concepts of Behavioral Medicine A Global Handbook - Fisher, Edwin B.; Cameron, Linda D.; Christensen, Alan J.; Ehlert, Ulrike; Guo, Yan; Oldenburg, Brian; Snoek, Frank J. (Springer New York : Imprint: Springer, 2018)
XIX, 1144 p. 63 illus., 36 illus. in color.